PENGARUH KUALITAS PELAYANAN, KEPERCAYAAN KONSUMEN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK SECARA ONLINE PADA APLIKASI LAZADA - Saifulloh, Ryan (Journal of Fundamental Management (JFM), 2023)
Price On Online Product Purchase Decisions On The Lazada Application. The research method is quantitative research and the type of research is explanatory research which aims to determine the cause and effect between the variables through hypothesis testing. The population in this study were all consumers using the Lazada application where the total population in this study was unknown. The sample used in this study were consumers using the Lazada application using a margin of error max. Data collection is done by using the method of questionnaires, documentation, library studies. This study uses grouping data based on variables and types of respondents, tabulating data based on variables from all respondents, presenting data for each variable being studied, performing calculations to answer the formulation of the problem and performing calculations to test the hypotheses that have been proposed. This study proves that service quality has an effect on purchasing decisions, trust has a positive and significant effect on purchasing decisions, price has an effect on purchasing decisions.